Mothers' Knowledge about Complementary Feeding Using the Baby Led Weaning (BLW) Method in Infants Aged 6-12 Months: A Descriptive Study - Urip, Arwini; Siswiyanti, Siswiyanti; Agustina, Lusinta (Poltekkes Kemenkes Surakarta, 2024)
Background: The period of complementary feeding is an important period in infant growth. One method that is currently developing is Baby Led Weaning (BLW), which is a method that allows infants to eat independently according to their motor skills without being spoon-fed. However, the success of this method is greatly influenced by mothers' knowledge of the principles, benefits, and risks of BLW. This study aims to determine mothers' knowledge of complementary feeding using the Baby Led Weaning method for infants aged 6–12 months. Methods: This study is a quantitative descriptive study with a cross-sectional approach. The population in this study consisted of all mothers who had infants aged 6–12 months in the working area of the Community Health Center where the study was conducted. The sample consisted of 40 respondents selected using purposive sampling. The research instrument was a questionnaire that had been tested for validity and reliability. The data were analyzed univariately and presented in the form of frequency distributions and percentages. Results: The results of this study show that of the 35 mothers, 16 mothers (45.7%) had good knowledge, 7 mothers (20%) had sufficient knowledge, and 12 mothers (34.3%) had poor knowledge. Conclusion: Mothers' knowledge of the BLW method is generally good, but there is a need for improved education regarding implementation techniques and food safety. Health workers are expected to provide counseling and practical guidance on the BLW method so that mothers can apply it correctly to support optimal infant growth and development.